GENDER AND MASCULINITY: RELATIONSHIPS AND CULTURAL PRACTICES - Gutiérrez Lozano, Saúl (2006)
The theoretical approach I argue for in this article is that masculinity and sexualityare both highly dependant on the social and cultural context where women andmen interact with one and other, rather than being byproducts of biological makeup or evolutionary psychological structures. This article suggests that the exerciseof sexuality, masculine sexual pleasure, and masculinity gain a particular meaningand significance within a set of married and familial relationships.